Development of a Halotolerant Community in the St. Lucia Estuary (South Africa) during a Hypersaline Phase - Carrasco, Nicola K.; Perissinotto, Renzo (PLOS ONE, 2012)
Background The St. Lucia Estuary, Africa's largest estuarine lake, is currently experiencing unprecedented freshwater deprivation which has resulted in a northward gradient of drought effects, with hypersaline conditions in its northern lakes. Methodology/Principal Findings This study documents the changes that occurred in the biotic communities at False Bay from May 2010 to June 2011, in order to better understand ecosystem functioning in hypersaline habitats. Few zooplankton taxa were able to withstand the harsh environmental conditions during 2010. These were the flatworm Macrostomum sp., the harpacticoid copepod Cletocamptus confluens, the cyclopoid copepod Apocyclops cf. dengizicus and the ciliate Fabrea cf. salina. In addition to their exceptional salinity tolerance, they were involved in a remarkably simple food web. In June 2009, a bloom of an orange-pigmented cyanobacterium (Cyanothece sp.) was recorded in False Bay and persisted uninterruptedly for 18 months. Stable isotope analysis suggests that this cyanobacterium was the main prey item of F. cf. salina. This ciliate was then consumed by A. cf. dengizicus, which in turn was presumably consumed by flamingos as they flocked in the area when the copepods attained swarming densities. On the shore, cyanobacteria mats contributed to a population explosion of the staphylinid beetle Bledius pilicollis. Although zooplankton disappeared once salinities exceeded 130, many taxa are capable of producing spores or resting cysts to bridge harsh periods. The hypersaline community was disrupted by heavy summer rains in 2011, which alleviated drought conditions and resulted in a sharp increase in zooplankton stock and diversity. Conclusions/Significance Despite the current freshwater deprivation crisis, the False Bay region has shown to be resilient, harboring a unique biodiversity with species that are capable of enduring harsh environmental conditions. However, further freshwater deprivation may extend beyond the physiological thresholds of this community, as well as other unique biodiversity components which this system sustains.